2020
DOI: 10.5114/fn.2020.94008
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of miR-155 attenuates neuropathic pain by inducing an M1 to M2 switch in microglia

Abstract: Introduction: The polarization state of microglia affects the progress of neuropathic pain. MiR-155 modulates polarization of microglia, while its role in neuropathic pain has not been well studied. Material and methods: We separately used lipopolysaccharide (LPS) and interleukin 4 (IL-4) for constructing an M1/M2 polarization model in BV-2 cells. The levels of CD86, iNOS, CD206, Arg and miR-155 were measured by western blot or qRT-PCR, as needed. Subsequently, BV-2 cells were transfected with miR-155 mimics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…On the one hand, miR-155 is linked to T cell dysregulation [ 87 ], another important feature of AD pathophysiology. Additionally, the suppression of miR-155 was demonstrated to promote the microglial switch from the M1 pro-inflammatory phenotype to the neuroprotective M2 phenotype [ 88 ]. On the other hand, data from earlier studies conducted on AD animal models might be confusing as the inhibition of miR-155 expression was shown to be correlated to increased Aβ plaque level at the cerebral level [ 56 ].…”
Section: Related Mechanisms and Future Research Directionsmentioning
confidence: 99%
“…On the one hand, miR-155 is linked to T cell dysregulation [ 87 ], another important feature of AD pathophysiology. Additionally, the suppression of miR-155 was demonstrated to promote the microglial switch from the M1 pro-inflammatory phenotype to the neuroprotective M2 phenotype [ 88 ]. On the other hand, data from earlier studies conducted on AD animal models might be confusing as the inhibition of miR-155 expression was shown to be correlated to increased Aβ plaque level at the cerebral level [ 56 ].…”
Section: Related Mechanisms and Future Research Directionsmentioning
confidence: 99%
“…Furthermore, SOCS1 induces differentiation from the M1 to M2 state and increased SOCS1 in the M2 phenotype, which plays an important role in sustaining the anti-inflammatory function [67]. Moreover, miR-155 can target M2-associated genes, and inhibition of miR-155 promotes the expression of M2 markers [68], such as Arg1, Ym1, and Fizz1. The above evidence suggests that the regulation of miR-124 and miR-155 in EAE has an important effect on the polarization of microglia, and the polarization of M1/M2 may also be accompanied by the changes of miR-124 and miR-155.…”
mentioning
confidence: 99%
“…In the present study, we found that DMY induced a switch from M1 to M2 phenotype polarization in microglia cells, which attenuates neuropathic pain. As neuropathic pain is mainly caused by M1 phenotype polarization, we constructed M1 phenotype polarization cells using LPS, as it is the common stimulator of M1 phenotype polarization (45,46). We further investigated the effects of DMY on M1/M2 phenotype polarization in the presence of LPS treatment, and found that the polarization of cells was increased with an increase in the DMY concentration in BV-2 cells.…”
Section: Discussionmentioning
confidence: 99%